Contribution to the study of the Peruvian wart - Battistini, Telémaco S. (1927)
Let us first of morphological appearance of this organism in colored preparations. The Giemsa, Wright and toluidine blue, lytic Mackehenie are the only dyes that allow accurate structural knowledge of Bb Frottis well fine, fixed at laboratory temperature, or methyl alcohol, are colored with Giemsa solution for 10 or 15 minutes, washed in a strong running water sweeping precipitates ocasionalemente are formed on the amorphous magma culture medium, and allowed to air dry.